Synchronization of fronto-parietal beta and theta networks as a signature of visual awareness in neglect - Yordanova, Juliana; Kolev, Vasil; Verleger, Rolf; Heide, Wolfgang; Grumbt, Michael; Schürmann, Martin (Elsevier, 2017)
In the neglect syndrome, the perceptual deficit for contra-lesional hemi-space is increasingly viewed as a dysfunction of fronto-parietal cortical networks, the disruption of which has been described in neuroanatomical and hemodynamic studies. Here we exploit the superior temporal resolution of electroencephalography (EEG) to study dynamic transient connectivity of fronto-parietal circuits at early stages of visual perception in neglect. As reflected by inter-regional phase synchronization in a full-field attention task, two functionally distinct fronto-parietal networks, in beta (15–25 Hz) and theta (4–8 Hz) frequency bands, were related to stimulus discrimination within the first 200 ms of visual processing. Neglect pathology was specifically associated with significant suppressions of both beta and theta networks engaging right parietal regions. These connectivity abnormalities occurred in a pattern that was distinctly different from what was observed in right-hemisphere lesion patients without neglect. Also, both beta and theta abnormalities contributed additively to visual awareness decrease, quantified in the Behavioural Inattention Test. These results provide evidence for the impairment of fast dynamic fronto-parietal interactions during early stages of visual processing in neglect pathology. Also, they reveal that different modes of fronto-parietal dysfunction contribute independently to deficits in visual awareness at the behavioural level.